PENGARUH COUNTRY OF ORIGIN, WORD OF MOUTH, KUALITAS YANG DIPERSEPSIKAN TERHADAP NIAT BELI: STUDY PADA KAMERA DIGITAL MEREK JEPANG - Purwanto, Edy; Wibisono, Aryo (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This study aims to test the influence of country of origin image and word of mouth on perceived quality. Then, the country of origin image and word of mouth and perceived quality on purchase intention of digital camera from Japan. The number of samples in this research are 230 respondents taken by purposive sampling method. Analysis of Structural Equation Modeling (SEM) is used to test the hypothesis. The results of this study showed that country of origin image and word of mouth have a positive and significant effect on perceived quality. Then, Word of mouth and perceived quality have a positive and significant effect on purchase intention but a country of origin image has no significant effect on purchase intention.